Responses of Ammonia-Oxidizing Microorganisms to Intercropping Systems in Different Seasons - Xingjia He (Agriculture, 2021)
Intercropping plays an essential role in agricultural production, impacting the soil’s physical and chemical properties and microbial communities. However, the responses of ammonia-oxidizing microorganisms in the continuous-cropping soil to different intercropping systems in different growing seasons are still insufficiently studied. Here, we investigated the effects of seven intercropping systems (alfalfa (Medicago sativa L.)/cucumber, trifolium (Trifolium repens L.)/cucumber, wheat (Triticum aestivum L.)/cucumber, rye (Secale cereale L.)/cucumber, chrysanthemum (Chrysanthemum coronrium L.)/cucumber, rape (Brassica campestris L.)/cucumber, mustard (Brassica juncea L.)/cucumber) on soil physical and chemical properties, potential nitrification rate (PNR), soil ammonia-oxidizing archaea (AOA), and ammonia-oxidizing bacteria (AOB) communities in the greenhouse in spring and autumn. The results showed that, compared with cucumber monoculture, intercropping increased the soil <semantics><msubsup>NH4+</msubsup></semantics>-N and <semantics><msubsup>NO3−</msubsup></semantics>-N. The chrysanthemum–cucumber, rape–cucumber, and mustard–cucumber treatments increased soil PNR. Intercropping increased the AOA and AOB abundances in two seasons, especially in rape–cucumber, wheat–cucumber, chrysanthemum–cucumber, and trifolium–cucumber treatments. The ratio of AOA and AOB decreased with seasonal variation. The wheat–cucumber and rape–cucumber treatments increased soil AOA community diversity. Seasonal variation had a significant effect on the relative abundance of the AOB community. Nonmetric multidimensional scaling analysis showed that the AOA and AOB community structures were obviously different from spring to autumn. Redundancy analysis showed that the AOA community was significantly regulated by moisture, <semantics><msubsup>NO3−</msubsup></semantics>–N, and available potassium (AK), while the AOB community was significantly regulated by moisture, available phosphorus (AP), AK, <semantics><msubsup>NO3−</msubsup></semantics>-N, and pH. Network analysis showed that the co-occurrence relationship and complexity of AOA and AOB communities were different in two growing seasons. The AOB community may play a critical role in ammonia oxidation in autumn. Taken together, intercropping improved soil physicochemical state, increased soil PNR and significantly altered soil AOA and AOB communities. Seasonal variation significantly altered the AOA and AOB communities’ structure and interaction between them. The effect of seasonal variation on AOA and AOB communities was greater than intercropping.